Penerapan Teknologi Iot Pada Prototype Sistem Jemuran Otomatis Menggunakan Sensor LDR dan Sensor Raindrop - Gilbert The Nyap Hong; Manorang Gultom; Paskalia Kartini (LPPM Universitas Widya Dharma Pontianak, 2025)
Drying clothes plays an important role in everyday life, if there is a sudden change in the weather, then the activity of drying clothes which is usually done outdoors manually becomes less effective when it suddenly rains. To overcome this problem, the use of internet of things (IoT) technology can provide convenience in controlling clothes drying. This study uses the Use Case Diagram (UML), Activity Diagram, and Sequence Diagram analysis techniques to design and model the system, for the data collection method a literature study was carried out in the form of books related to the research, while for programming the system prototype using software in the form of Arduino IDE and for making the clothes drying system control software was made using Kodular. This study produced a prototype of an automatic clothes drying system that can take out and put in clothes according to the selected mode and an android application that can be used to control the prototype of the automatic clothes drying system, for manual mode the clothes drying is controlled using the in and out buttons on the control application to control the clothes drying, for auto mode where the clothes will go in and out by itself according to the light intensity received on the ldr sensor and the water condition value on the raindrop sensor board. The conclusion obtained from this study is that the prototype clothesline system can automatically remove and insert clotheslines according to the selected mode.